Pengembangan Kreativitas Guru Pendidikan Anak Usia Dini (PAUD) Melalui Kegiatan Lomba Mendongeng - Andi Aslindah; Desmiati Lawing (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
A teacher must be creative, and professional in creating fun learning for their students in an effort to grow and develop the potential of their students. One form of creativity that teachers need to develop as potential in themselves is creativity in storytelling. Teacher creativity in storytelling is a very important skill for an early childhood education teacher to develop in himself as capital in facilitating fun learning according to the needs of his students. Therefore, teachers must hone their storytelling skills by using props or not using props. One of the efforts that teachers can make to improve their storytelling skills is to take part in storytelling training and storytelling competitions.